The Role of Brand Authenticity, Brand Image, and Brand Love in Driving Repurchases and Advocacy of Indonesian Fashion Brands - Kalyana, Azarine Nurfairuz (School of Business, IPB University (SB-IPB), 2025)
Background: In this era of globalization, as brand competition intensifies in Indonesia, companies must explore strategies to become consumers' top choice. Strengthening branding efforts is one of the options for local fashion brands to enhance their competitive advantage. By concentrating on effective branding strategies, local brands can distinguish themselves and excel in a saturated market.Purpose: This study aims to investigate the influence of multidimensional brand authenticity constructs (quality commitment, heritage, and sincerity), multidimensional brand image constructs (mystery, sensuality, and intimacy), brand love, and consumer behavior related to continuous purchase intention and positive word-of-mouth (WOM) in Indonesia.Design/Methodology/Approach: This research is quantitative-based, with data collection conducted through an online survey of 265 respondents who purchased products from Indonesian local fashion brands from October 2023 until April 2024. Data analysis was conducted using the Structural Equation Modeling (SEM) method through the SmartPLS application.Findings/Result: The study's findings indicate that intimacy, an emotionally driven dimension of brand image, significantly predicts brand love, continuous purchase intentions, and positive WOM. Furthermore, the study confirms that brand love itself predicts continuous purchase intentions and positive WOM.Conclusion: To achieve loyalty in the form of repeated purchases and positive WOM, Millennials and Generation Z consumers in Indonesia need to experience the stage of affection towards a certain Indonesian local fashion brand, rather than the cognitive or sensory aspects.Originality/Value: This study intends to give a better understanding of several branding-related constructs in the Indonesian local fashion brand setting that can be utilized by marketers to develop consumer-brand relationships with a younger customer base (Millennials and Generation Z), which leads to continuous consumption and spreading positive news. Keywords: brand love, brand authenticity, brand image, repurchase intention, positive word-of-mouth